Antibacterial and anti-inflammatory activities of Cassia fistula fungal broth-capped silver nanoparticles. (6th December 2021) - Jyoti, Kumari; Arora, Devender; Fekete, Gusztáv; Lendvai, László; Dogossy, Gábor; Singh, Tej
ABSTRACT: The growing need for sustainable technologies has attracted considerable interest in the synthesis of ecofriendly materials. This paper reports the anti-inflammatory and antibacterial activities of sustainable silver nanoparticles (AgNPs) fabricated using endophytic fungus extracted from a medicinal plant, Cassia fistula . Fourier transform-infrared and UV-visible were used for AgNPs characterisation. X-ray diffraction, scanning electron microscope, energy dispersive X-ray analysis, atomic force microscope (AFM), transmission electron microscope and dynamic light scattering analysis revealed that the biosynthesised AgNPs were within the size of ~4–54 nm. The synthesised AgNPs displayed considerable antibacterial activity against Staphylococcus aureus, Escherichia coli and Klebsiella pneumonia bacterial strains. Additionally, synthesised AgNPs showed significant anti-inflammatory potential.